Identification of mcr-8 in Clinical Isolates From Qatar and Evaluation of Their Antimicrobial Profiles - Eltai, Nahla O.; Kelly, Brianna; Al-Mana, Hassan A.; Ibrahim, Emad B.; Yassine, Hadi M.; Al Thani, Asmaa; Al Maslmani, Muna; Lammens, Christine; Xavier, Basil B.; Malhotra-Kumar, Surbhi (Frontiers in Microbiology, 2020)
This study was performed to investigate the genotypic causes of colistin resistance in 18 colistin-resistant K. pneumoniae (n=13), E. coli (n=3) and P. aeruginosa (n=2) isolates from patients at the Hamad General Hospital in Qatar. MIC testing for colistin was performed using Phoenix (BD Biosciences, Heidelberg, Germany) and then verified with SensiTest Colistin (Liofilchem, Zona Ind. le, Italy). Strains determined to be resistant (MIC >4 -16 µg/mL) were then whole genome sequenced (MiSeq, Illumina Inc.). Sequences were processed and analyzed using BacPipe, a bacterial whole genome sequencing analysis pipeline. Known chromosomal modifications were determined using CLC Genomics Workbench v.9.5.3 (CLCbio, Denmark). Two K. pneumoniae isolates (KPN-15 and KPN-19) harboured mcr-8 on the IncFII(K) plasmids, pqKPN-15 and pqKPN-19, and belonged to ST383 and ST716, respectively. One E. coli strain harboured mcr-1.1 on the IncI2 plasmid pEC-12. The other 15 strains harboured known chromosomal mutations linked to colistin resistance in the PhoPQ two-component system. In addition, three K. pneumoniae strains (KPN-9, KPN-10 and KPN-15) showed disruptions due to IS elements in mgrB. To our knowledge, this marks the first description of mcr-8 in K. pneumoniae of human origin in Qatar. Currently more research is necessary to trace the source of mcr-8 and its variants in humans in this region.